Monetary Integration in The European Union: Problems and Challenges - Mariusz TOMCZYK; Tomasz KOSCIELECKI (Communications of International Proceedings, 2022)
The process of monetary integration in Europe is closely related to the process of economic integration. It is commonly believed that the creation of the area of the common European currency was a consequence of primarily economic reasons. Theoretically, the euro was supposed to be the power of an efficient and development-able economic system comparable in scope to the US economy. In practice, however, this was not the case. The aim of the article is to present the issues of monetary integration in the European Union.
Keywords: economy; monetary integration; Euro currency.